Metode Air Terjun pada Sistem Informasi Studio Musik (Studi Kasus : Watakham Studio Palangka Raya) - Rosmiati, Rosmiati; Sulistyowati, Sulistyowati; Hendartie, Susi; Nugroho, Bayu Prataman; Sam'ani, Sam'ani; Rudini, Rudini; Nizar, Muhammad (Jurnal Sains Komputer dan Teknologi Informasi, 2025)
Watakham Studio, a music studio operating in Palangka Raya, currently manages rental data manually, which can lead to recording errors, service delays, and difficulties in data archiving. This research aims to design and develop a music studio rental information system using the Waterfall method. This method is chosen due to its systematic approach, consisting of the following phases: requirements analysis, system design, implementation, testing, and maintenance. The developed information system focuses on the digital management of rental schedules, customer data, and transaction reports. A case study was conducted directly at Watakham Studio to ensure the system meets the real needs of users. The implementation results show that the system can accelerate operational processes, reduce the risk of errors, and improve service efficiency. By applying the Waterfall method, the developed information system operates according to the initial design and has a positive impact on studio management.